2016
DOI: 10.1186/s12889-016-3896-x
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence against married rural-to-urban migrant workers in eastern China: prevalence, patterns, and associated factors

Abstract: BackgroundIntimate partner violence (IPV) is a significant public health issue among married rural-to-urban migrant workers, the largest group of internal migrants in China. This study aims to explore the prevalence, patterns and associated factors of intimate partner violence against married rural-to-urban migrant workers in eastern China.MethodsA cross-sectional study was conducted in Zhejiang province in China between July 2015 and April 2016, and a total of 1,744 married rural-to-urban migrant workers ulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…For instance, Tu and colleagues (2014) sampled 958 rural-to-urban migrant women in Shanghai and found that approximately 40% of the participants reported having experienced IPV in their lifetime. Another study that surveyed 1,744 married migrants in four cities in Zhejiang, an eastern coastal province in China, reported a rate of IPV of 44.2% in the past 12 months, and migrant women were more likely to experience sexual IPV compared to their male counterparts (Chen et al, 2016). Although these estimates are not representative of all urban-based migrant women, they suggest the seriousness of the issue of IPV among this population.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For instance, Tu and colleagues (2014) sampled 958 rural-to-urban migrant women in Shanghai and found that approximately 40% of the participants reported having experienced IPV in their lifetime. Another study that surveyed 1,744 married migrants in four cities in Zhejiang, an eastern coastal province in China, reported a rate of IPV of 44.2% in the past 12 months, and migrant women were more likely to experience sexual IPV compared to their male counterparts (Chen et al, 2016). Although these estimates are not representative of all urban-based migrant women, they suggest the seriousness of the issue of IPV among this population.…”
Section: Introductionmentioning
confidence: 98%
“…The decrease in the sex ratio (male-to-female ratio, 15 and 64 years old) in the internal migrant population in China has reflected this trend: from 1.31:1 in 1990 to 1.18:1 in 2015 (UNFPA, 2019). With the backdrop of the ongoing domestic migration, in the field of IPV research in China attention has now been given to the prevalence of intimate partner violence (IPV) among migrant populations in urban areas (e.g., Chen et al, 2016;Tu & Lou, 2017). For instance, Tu and colleagues (2014) sampled 958 rural-to-urban migrant women in Shanghai and found that approximately 40% of the participants reported having experienced IPV in their lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that intimate partner violence (IPV) occurs frequently around the world, cutting across all socioeconomic, cultural, and religious boundaries (Chen et al, 2016; García-Moreno et al, 2005, 2006; Ogland et al, 2014; Wong et al, 2016, 2013; Xu, 1997; Xu et al, 2011, 2019; Zhang et al, 2019; Zhang & Zhao, 2018; Zheng et al, 2019). More importantly, multiple strands of evidence show that IPV victimization is associated with a myriad of pernicious physical, mental, and reproductive health outcomes globally, which is particularly pronounced for women who have experienced either lifetime or past year/month IPV (Garcia-Moreno et al, 2006; Wong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…IPV is considered to be a major type of violence in the recent legislation on domestic violence in China. Recent studies found that the prevalence rate of preceding-year IPV against women ranged from 7.7% to 55% among different population groups in China (L. Chen, Yu, Luo, & Huang, 2016; Fulu, Jewkes, Roselli, & Garcia-Moreno, 2013; Hou, Cerulli, Wittink, Caine, & Qiu, 2018; T.…”
Section: Introductionmentioning
confidence: 99%